Ingenieurholzbau - Grundlagen der Bemessung - Blaß, Hans JoachimSandhaas, Carmen (KIT Scientific Publishing, 2016)
This comprehensive book provides in-depth knowledge and understanding of design rules according to Eurocode 5. It is based on the first edition of the STEP-series, the Structural Timber Education Programme, which has been prepared in 1995 by about 50 authors from 14 European countries. The present book is an updated and extended edition and is of interest to students, structural engineers and other practitioners dealing with timber structures.